New inversion formulas for the Krätzel transformation - Domingo Israel Cruz-Báez; José Rodríguez Expósito (International Journal of Mathematics and Mathematical Sciences)
We study in distributional sense by means of the kernel method an integral transform introduced by Krätzel. It is well known that the cited transform generalizes to the Laplace and Meijer transformation. Properties of analyticity, boundedness, and inversion theorems are established for the generalized transformation.